Design and Implementation of a Knee Rehabilitation Device - Jabbar, Athraa Abdul Razzaq; Hamid, Mohammed ihsan Mohammed; Saddam, Sajad Adnan Abdul Qader; knus, Dema khalil ibrahem (American Journal of Botany and Bioengineering, 2025)
Rehabilitation procedures aim to regain normal bodily functions and promote independence in daily living activities while enhancing the limbs’ remaining sensorimotor functions. The project consist of a mechanical part that used to move the leg and a control panel used to control the device from time and the strength of the move. The test results shown a good accuracy about 77% according to the tests that made on a healthy male aged 21 years old. For future work it will be add a microcontroller to control the system and add an ankle test rehabilitation.